The Effect Of Needs For Performance, Affiliation, And Domination On The Motivation Of Coastal Women Business In Aceh Province - Muksal Muksal; Arroyyan Ramly; M Shabri Abd Majid; Mirna Indriani (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to analyze the effect of Variables of Performance, Affiliation, and Domination on the motivation of women living in coastal areas doing business in Aceh Province. The population in this study are Coastal Women who do business in Aceh Province by selecting samples using a purposive sampling technique with the criteria Women who do business have fishermen husbands, live on the coast in Aceh Province. The hypothesis is tested using multiple regression tests to determine whether an independent variable influences the motivation of coastal women to see how the overall relationship between Performance, Affiliation, and Domination affects women's motivation to do business in Aceh Province. The results show simultaneously that the effects of the three Performance Variables (X1), Affiliation (X2) and Domination (X3) significantly influence Women's Work Motivation. Based on the regression coefficients Variable Performance (X1), Affiliation (X2) and Domination (X3) partially there is a positive and significant influence on the Motivation of Women's Business Work in Aceh Province.